REPORT OF THE ANNUAL CONVENTION. - Walgenbach, Paul H. (The Accounting Review, 1963)
Abstract 1962 annual meeting of the American Accounting Association was held at East Lansing, Michigan on August 27-29, 1963 with the College of Business and Public Service of Michigan State University as host. The meeting was one of the largest and most successful in the history of the Association. A number of interesting tours and special luncheons were provided for ladies attending the meeting, and special programs were arranged for teenagers and children, including dances, movies, swimming, and educational campus tours. At the luncheon and business meeting president Raymond C. Dein presided and gave a report on Association activities for the year. A motion to accept the report of the Nominations Committee was made from the floor and carried, instructing the Secretary-Treasurer to cast a unanimous ballot for the foregoing slate of nominees. At the banquet on the same evening, Dein introduced the officers and guests at the speakers table and the newly elected 1963 officers.